Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Pegawai di Kantor Pertanahan Kota Ternate - Lisani, Dina; Jannang, Abdul Rahman (Jurnal MS, 2022)
Objective: The purpose of this study are: (1) Analyzing the influence of Style Leadership on the Employee Performance of Ternate City Land Office; (2) Analyzing the influence of Work discipline on the Employee Performance of Ternate City Land Office; and (3) Analyzing the influence of style leadership and Work discipline a simultaneously on the Employee Performance of Ternate City Land Office. The number of samples is 42 employees. Methodology: The test equipment used is multiple regression analysis using statistical package for social scientists (SPSS) as a statistical test tool. Finding: H1, H2, and H3 are accepted at the 5% confidence level. Conclusion: The results showed that: (1) Style Leadership has a positive and significant impact the Employee Performance of Ternate City Land Office. It is based on a t value greater than the value of t table, and a smaller significant value of alpha (Î±); (2) Work discipline has a positive and significant impact the Employee Performance of Ternate City Land Office. It is also based on a tvalue greater than the value of t table, and a significantly smaller value of alpha (Î±); and (3) Style Leadership and Work discipline simultaneously have a positive and significant influence the Employee Performance of Ternate City Land Office. It is based on the F value count greater than the F table value, and the significant value smaller than alpha (Î±).